Paradoxes of US-Pakistan Relationship: A Cost-Benefit Assessment of US Aid to Pakistan in Post-9/11 Era - Muhammad Riaz Shad; Yumna Rashid; Amir Mustafa (ASIAN Journal of International Peace & Security (AJIPS), 2024)
The US-Pakistan relationship, patterned on the centre-periphery disharmony, has gone through cyclical periods of cooperation and estrangement. In this course, the relationship follows a paradoxical pattern of strategic divergence even during the period of cooperation. In this context, Pakistan receives economic and military assistance from the US in return for playing a role in the latter’s geopolitical pursuits. However, this transactional cooperation carries another paradox pertaining to the benefits and costs of the US assistance for Pakistan. This research is qualitative in nature and follows the technique of thick description to identify and analyze various paradoxical patterns of the US-Pakistan relationship. Data has been collected from both primary and secondary sources. This article identifies various paradoxes in the US-Pakistan relationship with focus on the benefits and costs of the US assistance for Pakistan in post-9/11 period. It argues that disadvantages of the US assistance to Pakistan outweigh the advantages when the direct and indirect cost incurred by the latter is taken into account. Therefore, aid based on a long-term US-Pakistan partnership is the way forward.